Global kinome profiling reveals DYRK1A as critical activator of the human mitochondrial import machinery - Walter, Corvin; Marada, Adinarayana; Suhm, Tamara; Ernsberger, Ralf; Muders, Vera; Kücükköse, Cansu; Sánchez-Martín, Pablo; Hu, Zehan; Aich, Abhishek; Loroch, Stefan; Solari, Fiorella Andrea; Poveda Huertes, Daniel; et al. (Nature Communications, 2021)
The translocase of the outer mitochondrial membrane TOM constitutes the organellar entry gate for nearly all precursor proteins synthesized on cytosolic ribosomes. Thus, TOM presents the ideal target to adjust the mitochondrial proteome upon changing cellular demands. Here, we identify that the import receptor TOM70 is targeted by the kinase DYRK1A and that this modification plays a critical role in the activation of the carrier import pathway. Phosphorylation of TOM70Ser91 by DYRK1A stimulates interaction of TOM70 with the core TOM translocase. This enables transfer of receptor-bound precursors to the translocation pore and initiates their import. Consequently, loss of TOM70Ser91 phosphorylation results in a strong decrease in import capacity of metabolite carriers. Inhibition of DYRK1A impairs mitochondrial structure and function and elicits a protective transcriptional response to maintain a functional import machinery. The DYRK1A-TOM70 axis will enable insights into disease mechanisms caused by dysfunctional DYRK1A, including autism spectrum disorder, microcephaly and Down syndrome.